The politics of war powers : the theory & history of presidential unilateralism - Burns, Sarah (Sarah Mackenzie) (American political thought., 2019)
"Presidential war powers have greatly expanded over the last half-century as presidents increasingly initiate acts of war without the prior authorization of Congress and without facing serious consequences. The breakdown in the system of checks on executive power presents a constitutional problem, which has elicited significant scholarly attention in recent years. Sarah Burns looks to the theoretical roots of the separation of powers system in the writings of Montesquieu for guidance in addressing the current crisis. Montesquieu's complex moderate constitutionalism requires both the executive and legislative branches to make public arguments about war and compete for public approval. His argument for the necessity of the struggle between political branches leads to clearer checks on power and fewer rash military operations. The Politics of War Powers demonstrates the link between Montesquieuan and American government and argues that reintegrating Montesquieu's constitutionalism into American politics will provide a healthier model of interaction and dialogue between the President and Congress"--